(untitled) (Journal of Plant Disease Sciences, 2023)
Colletotrichum leaf spot is always regarded as a limiting factor for quantitative and qualitative losses of turmeric throughout the country. As a result, the current study on the efficacy of various fungicides and bio-agents against C. capsici under laboratory conditions was conducted to determine the most effective treatments. Using the poison food method, six different fungicides were tested in vitro against C. capsici. Among six fungicides tested, Tebuconazole 5.4 w/w FS, Carbendazim 12% + Mancozeb 63% WP, Azoxystrobin 18.2 w/w + Difenoconazole 11.4 w/w SC, Carboxin 37.5% + Thiram 37.5% DS inhibited 100% mycelial growth inhibition of C. capsici. The bio-agent was tested against C. capsici using the dual culture method. Trichoderma harzianum was found to be the most effective as a bioagent, with a maximum inhibition of mycelial growth of (68.66%) followed by T. asperellum with (68.36%), Pseudomonas fluroscens (64.29%) and Bacillus subtilis (60.24%).